Communication,navigation and IoT integration 5G indoor communication network - Xinwang ZHANG; Jia DONG; Sichen ZOU; Dong WANG; Wei DENG; Haiyu DING (Dianxin kexue, 2019)
In the 4G era,operators have become data service pipelines,while they will actively seek business transformation in the 5G era.According to research institutes,the indoor positioning and IoT market have broad prospects,and operators are working hard to expand vertical industry applications in related fields.However,the existing indoor communication network has a single function and cannot effectively support indoor positioning and IoT services.A communication,navigation and IoT integration 5G indoor communication network was proposed.By integrating the bluetooth module inside the indoor antenna,it achieved some new functions,such as downlink bluetooth positioning,advertisement information push,path loss detection,uplink IoT collection and uplink bluetooth positioning.The proposed technical solution can be applied to smart medical scenarios,such as smart consultation,equipment management,security management,logistical support and one-click alarm.